Intracellular and extracellular effector activity of mouse neutrophils in response to cutaneous and visceral Leishmania parasites - Valerio-Bolas, Ana (2019)
Neutrophils are short-lived phagocytic cells equipped with several receptors for pathogen recognition and phagocytosis and have intracellular and extracellular effector mechanisms that can inactivate pathogens. Leishmaniases are diseases caused by different species of Leishmania that mainly afflicts poorer populations of tropical and subtropical regions and immunocompromised individuals. Thus, the present study aims to investigate the effector response of murine neutrophils to species of Leishmania causing American cutaneous leishmaniasis and zoonotic visceral leishmaniasis by evaluating pattern recognition receptors (PRR) and intracellular and extracellular effector microbicide activity. When exposed to Leishmania parasites, mouse neutrophils produced superoxide, released enzymes in the extracellular space and generated neutrophil extracellular traps, although PRR gene expression is negatively regulated. L. infantum, L. guyanensis, and L. shawi inhibited enzymatic activity, whereas L. amazonensis reduced the emission of extracellular structures. These findings indicate that although neutrophils trigger several microbicide mechanisms, Leishmania parasites can manipulate extracellular effector mechanisms. The present study also provides evidence that neutrophils can internalize parasites by coiling phagocytosis.